Pulmonary fat embolism in non-survivors after cardiopulmonary resuscitation - Ihnát Rudinská, Lucia; Delongová, Patricie; Vaculová, Jana; Farkašová Iannaccone, Silvia; Tulinský, Lubomír; Ihnát, Peter (Forensic science international, 2024)
BACKGROUND: Blunt trauma acting against the human body presents the fundamental cause of pulmonary fat embolism (PFE) and fat embolism syndrome. The aim of the present study was to investigate PFE in non-survivors after cardiopulmonary resuscitation (CPR). METHODS: This was a prospective cohort study conducted in University Hospital Ostrava, Czech Republic. Within a 4-year study period, all non-survivors after CPR because of out-of-hospital cardiac arrest were assessed for the study eligibility. The presence/seriousness of PFE was determined by microscopic examination of cryo-sections of lung tissue (staining with Oil Red O). RESULTS: In total, 106 persons after unsuccessful CPR were enrolled in the study. The most frequent cause of death in the study population (63.2% of cases) was cardiac disease (ischemic heart disease); PFE was not determined as the cause of death in any of our study cases. Sternal fractures were identified 66.9%, rib fractures (usually multiple) in 80.2% of study cases; the median number of rib fractures was 10.2 fractures per person. Serious intra-thoracic injuries were found in 34.9% of cases. Microscopic examination of lung cryo-sections revealed PFE in 40 (37.7%) study cases; PFE was most frequently evaluated as grade I or II. Occurrence of sternal and rib fractures was significantly higher in persons with PFE than between persons without PFE (p = 0.033 and p = <0.001). Number of rib fractures was also significantly higher in persons with PFE. The occurrence of serious intra-thoracic injuries was comparable in both our study groups (p = 0.089). CONCLUSIONS: PFE presents a common resuscitation injury which can be found in more than 30% of persons after CPR. Persons with resuscitation skeletal chest fractures have significantly higher risk of PFE development. During autopsy of persons after unsuccessful CPR, it is necessary to distinguish CPR-associated injuries including PFE from injuries that arise from other mechanisms.
Keywords: kardiopulmonální resuscitace; CPR-associated injuries; Cardiopulmonary Resuscitation; Pulmonary fat embolism; lidé; Rib Fractures; Cardiac massage; Pulmonary Embolism; Resuscitation; prospektivní studie; plicní embolie; Prospective Studies; Rib fractures; fraktury žeber; embolie tuková; Embolism, Fat; Thoracic Injuries; poranění hrudníku; Humans